Chancroid and Haemophilus ducreyi: an update - David L. Trees; Stephen A. Morse (1995)
Haemophilus ducreyi is a fastidious gram-negative bacillus that causes the sexually transmitted infection chancroid. Chancroid is a major genital ulcerative disease in Africa, Southeast Asia, the Caribbean, and Latin America and is of increasing concern in the United States. Genital ulcerative disease and chancroid in particular have been associated with facilitating the transmission of human immunodeficiency virus. The diagnosis of chancroid based on the clinical appearance of the genital lesion or on the isolation of H. ducreyi on selective medium is relatively insensitive. However, recent advances in nonculture diagnostic tests have enhanced our ability to diagnose chancroid. There has been renewed interest in understanding the pathogenesis of H. ducreyi. In vitro and in vivo models have been developed to help identify important virulence determinants. Through the use of biochemical and molecular techniques, macromolecular components that may be important in virulence have been identified.